¿Fidelidad o adulterio?: los nudos conflictivos de la transposición de "Memorias de un wing derecho" (1985), de Roberto Fontanarrosa, en Metegol (2013), de Juan José Campanella. Issue 3 (2nd September 2019) - Hortiguera, Hugo
ABSTRACT: Taking into account the works of Linda Hutcheon, Sergio Wolf and Eliseo Verón on adaptation, this article explores the connections that the children's animation film Metegol (directed by Juan José Campanella and co-scripted with Eduardo Sacheri, 2013) establishes with "Memorias de un wing derecho" (Memories of a right wing footballer) by Roberto Fontanarrosa. Particular attention is paid to the film's production context and its consumption in a period marked by a pervasive binary vision of Argentine society (Fernández de Kirchner's administration). It also analyzes the relations of textual fidelity/infidelity with Fontanarrosa's story, and its process of mutation, (re)interpreting and (re)creation to describe the new social environment of Argentina in which Metegol was produced. It concludes that the relationship with the short story is presented as a meditation on the effects of enunciation in a cultural, social and political context characterized by an ideology of confrontation. It also brings into discussion the discursive construction of otherness.